Pengaruh Iklan “Shopee Versi COD” Terhadap Minat Beli Melalui Aplikasi Shopee Dikalangan Mahasiswa Program Studi D3 Administrasi Bisnis Politeknik Negeri Samarinda - Johan Lucas Away; ST. Nurhasanah; Ella Hariani (E-BISMARK : Jurnal Ekonomi, Bisnis Dan Marketing, 2022)
The marketing strategy that is currently being used is promotion through advertising. Advertising itself is a communication process that has an important power as a marketing tool in selling goods, providing services, and ideas through certain channels in the form of persuasive information. This study aims to analyze the influence of Shopee Advertisements "Shopee COD" version of the buying Interest through of Samarinda State Polytechnic Business Administration Students. The data of this study were obtained from a questionnaire (primary) distributed to students of the Department of Business Administration with the Purposive Sampling method. The population of this study was 412 students of the Department of Business Administration, the sample used in this study was 203 respondents. The classic assumption test used is the normality test. The hypothesis test used is simple linear regression.The results of this study indicate that there is a partial influence of Shopee Ads version of "Shopee COD" on the online buying interests of Business Administration students. Based on the coefficient of determination test (R2) stated Shopee Advertising has a contribution to online buying interest of 42.8% and the remaining 57.2% is influenced by other factors outside the study